Effect of Pouteria sapota kernel meal on in vitro ruminal fermentation, nutrient degradability, and protozoa population - Sánchez-Zárate, Adriana; Chay-Canul, Alfonso Juventino; Aguilar-Urquizo, Edgar; Canul-Solis, Jorge; Giácoman-Vallejos, German; González-Sánchez, Avel; Hernández-Núñez, Emanuel; Pérez-Gutiérrez, Alfonso; Bautista-Parra, San German; Vargas-Bello-Pérez, Einar; Piñeiro Vázquez, Angel Trinidad (Chilean Journal of Agricultural & Animal Sciences, 2024)
This study determined the effect of different levels of mamey kernel meal (MKM) as a substitute for ground corn and soybean meal on in vitro gas production, nutrient degradability, fermentation, and protozoan population. The study was carried out in a randomized block design repeated over time. The treatments consisted of seven levels of mamey kernel meal, namely 0, 5, 10, 15, 20, 25, and 30% dry matter (DM), replacing ground corn and soybean meal. The inclusion of MKM had a linear effect on in vitro gas production (P=0.03); the highest production was at 30% inclusion and the lowest at 0%, with 381 and 291 mL g-1, respectively. No differences (P>0.05) were found in gas production, fermentation rate, and lag time between treatments. The maximum volume of gas production (397.43 mL g-1) was at 30%, while the lowest (291.40 mL g-1) was observed at 0% inclusion of MKM. No differences were found in nutrient degradability, protozoan population, and volatile fatty acids (P>0.05). The genera of protozoa that were identified were Entodinium and Holotrich. The different inclusion levels of MKM did not affect the total protozoa population (P>0.05). In conclusion, MKM can be included up to 15% under in vitro conditions without negative effects on fermentative parameters. However, further in vivo studies are needed.